Incidencia de la gestión de personal en la satisfacción del talento humano de la empresa lácteos la polaca gustalac s.a. de la ciudad de Quevedo, año 2023. - Alvarado Cobeña , Yuri Valeria (2024)
Companies are aware that human talent is their main resource, therefore, they try to generate a pleasant work environment to promote coordinated work among the participants of the institution, due to the commitment of the staff to the company, this promotes generation of greater labor productivity. In this sense, this research entitled “Incidence of personnel management on the satisfaction of human talent of the company Lácteos la Polaca Gustalac S.A. of the city of Quevedo, year 2023”, the objective of the research being to evaluate personnel management and its impact on the satisfaction of the human talent of the company Lácteos la Polaca Gustalac S.A. of the city of Quevedo, where the administration process will be investigated, which includes recruitment, selection, hiring and induction, job satisfaction and performance evaluation that are fundamental to achieve effective management that leads to keeping staff satisfied and motivated with their work. in their work space, thus preventing people who occupy a place within the company from leaving it, allowing the competition to take advantage of trained human talent, which can swell the ranks of the competition or other factors at the level of the organizations.